THE ONLINE ENGLISH LEARNING DURING PANDEMIC AT THE FOURTH SEMESTER ENGLISH LANGUAGE EDUCATION PROGRAM STUDENTS OF INSTITUT PENDIDIKAN TAPANULI SELATAN - Gabby Maureen Pricilia; Habib Rahmansyah (Institut Pendidikan Tapanuli Selatan, 2021)
COVID-19 pandemic makes the learning activities must be shifted into online learning. This research aim is to describe the implementation of online english learning during pandemic at the English Education Program students of Institut Pendidikan Tapanuli Selatan in 2020/2021 Academic Year. The type of this research is qualitative research. Questionnaire is the technique of collecting data with the subject of this research is 10 English Education Program students at the fourth semester. Then the data is analyzed in three steps; data condensation, data display and conclusion. The findings show that the implementation of online english learning which divided in three aspects, they are lesson planning is 69.8%, it is categorized good, the learning process is 58.2%, it is categorized enough and the learning material is 60.4%, it is categorized good. It means that the implementation of online english learning at english language education program in Institut Pendidikan Tapanuli Selatan is good for planning and material, enough for the process. Therefore it needs improvement in english online learning process to make students understand and enjoy the class.